Ken McGee: capstone - McGee, Ken, artist (Colorado State University. Libraries, 2015)
The artist's statement: I am a designer and illustrator currently in my fourth year studying Graphic design at Colorado State University. I enjoy design and illustration for their distinctive qualities; illustration for its story, for the emotion in the images, and design for the craft, for the character of its use. In my work I explore themes of intimacy and emotion, as well as an ephemeral quality to the subjects of my drawings. I create images which evoke feelings that are sometimes sensual and intimate and sometimes monumental, working through a foggy, distant and unfocused aesthetic, inspiring a sense of silence and loneliness. My fascination with these themes in part comes from growing up in Wyoming and experiencing the vastness of the plains and the depth of their silence.
Colorado State University Art and Art History Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.